De vozes e ciclos: o poema encarnado de Sónia Sultuane - Aquino, Inaldo da Rocha (2022)
This dissertation aims to analyze the poetry collection Roda das Encarnações (2017) by the Mozambican poet Sónia Sultuane, showing that the incarnate poem of that writer is structured from an aesthetic and ideological discussion about voice, spirituality and life cycles. Therefore, the investigation makes use of a dialogue between poetry of incarnation in the feminine and Mozambican religiosities. To support the research, we followed the discussions by Paradiso (2019), (2015) and Awolalu (2005) on religiosity, literature and traditional beliefs in Mozambican territory; de Cooper (1998) and magical realism; Opuko (2010) and his contribution to the study of historical religious formation in Mozambique, Hampaté Bâ (2010) and ancestral oral tradition; followed by Freitas (2020, and her collaboration with the studies of female authorship in Mozambique, as well as by Pinheiro (2021) with regard to Mozambicanity and the formation of the literary canon. Sultuane's work moves towards a multifaceted connection with the universe of the arts. The final analyzes of the corpus show us that the literary persona of Sónia Sultuane walks closely linked to the incarnation cycles that the collection suggests and the poetic voices that appear in the verses bring the representation of a multifaceted spirituality that circulates different flows of embodied experiences.